Reliability and availability analysis for robot subsystem in automotive assembly plant: A case study - Fudzin, A.F. (Institute of Physics Publishing, 2015)
The automotive assembly plant in a manufacturing environment consists of conveying systems and robots. Robots with high reliability will ensure no interruption during production. This study is to analyze the individual robot reliability compared to reliability of robots subsystem in series configuration. Availability was computed based on individual robots breakdown data. Failures due to robots breakdown often occurred during the operations. Actual maintenance data for a period of seven years were used for the analysis. Incorporation of failures rate and mean time between failures yield the reliability computation with the assumption of constant failure rate. Result from the analysis based on 5000 operating hours indicated reliability of series configuration of robots in a subsystem decreased to 2.8 in comparison to 38 reliability of the individual robot with the lowest reliability. The calculated lowest availability of the robots is 99.41. The robot with the lowest reliability and availability should be considered for replacement.